AB0770 Differential Extracellular Protein Profiles of Osteoarthritic and Normal Mesenchymal Stem Cells Undergoing Chondrogenesis by the Double-Silac Technique. (10th June 2014) - Rocha, B.; Calamia, V.; Casas, V.; Lourido, L.; Fernández, C.; Carrascal, M.; Ruiz-Romero, C.; Blanco, F.J.
Abstract : Background: Chondrogenesis occurs as a result of mesenchymal stem cells (MSCs) condensation and chondroprogenitor cell differentiation. Following chondrogenesis, the chondrocytes remain as resting cells to form the articular cartilage. A major challenge for the osteoarthitic (OA) cartilage reparation by stem cell-based approaches is the understanding of this multi-step process. Objectives: To analyse the extracellular protein expression profile of human bone marrow MSCs (hBMSCs) of osteoarthritic patients and control donors undergoing chondrogenesis, in order to compare the mechanisms involved in the cartilage extracellular matrix (ECM) remodeling that occurs during the chondrogenic differentiation process. Methods: hBMSCs isolated from 3 OA patients and 3 healthy controls were grown with different isotope variants of lysine and arginine (Arg6, Lys4 for the control population and Arg10, Lys8 for the OA population) during 4-6 weeks, until achievement of full protein labeling. The labeled populations were then subjected to differentiation in 3D cultures (micromasses) supplemented with chondrogenic inducers for 14 days. Proteins in the conditioned media from the two cell populations were combined, separated by 1D-SDS-PAGE and subjected to in-gel trypsin digestion using an automatic digestor. The resulting peptide mixtures were analyzed by nanoLC coupled on-line to an LTQ-Orbitrap XL mass spectrometer and quantified using the MaxQuant software and the Perseus tool. Results: Real-Time PCR assays showed a relevant difference in the gene expression of collagen type II in the normal donors when compared to the OA patients. Moreover, the chondrocyte phenotype was confirmed in both cases by the proteglycan immunostainings such as aggrecan and chondroitin-6-sulfate after 14 days in chondrogenesis. Using the proteomic approach, we compared the extracellular protein profiles of OA and normal hBMSC at the same time of differentiation. Among the 531 proteins, 56 had significantly altered levels. 35 proteins displayed consistently higher levels in the OA samples compared to normal donors. Many of these proteins are cartilage specific proteoglycans such as hyaluronan and proteoglycan link protein 1, aggrecan core protein or lumican as well as some proteins with a well-known role in the pathogenesis of OA like COMP or MMP3. On the other hand, 21 proteins exhibited a significantly reduced abundance in OA patients when compared to controls. Interestingly, we detected several proteins which belong to the tenascin protein family, like tenascin-X, which accelerates collagen fibril formation. We also found WISP2 decreased at day 14, suggesting a lower activity of the Wnt signaling pathway in OA cells. Conclusions: The identification and quantification of these secreted proteins enhance our knowledge on the extracellular regulation of the chondrogenesis and allow the identification of extracellular markers of this process. Moreover, the lower expression of some of them in OA patients (like tenascin-X or WISP2), suggest their putative usefulness for the molecular monitorization of the chondrogenesis in cell therapy-based approaches for cartilage repair. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4997